TANGGUNG JAWAB HUKUM PETUGAS FISIKAWAN MEDIS TERHADAP KUALITAS MUTU PADA IZIN OPERASIONAL RADIOLOGI DI RUMAH SAKIT BHAYANGKARA BANDA ACEH - Yohny Anwar; T. Riza Zarzani; Chermanto Chermanto (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Medical physicists are professionals who apply the principles of Medical Physics in their practice. They work in healthcare facilities, academic institutions, or research organizations after undergoing structured education and training. Medical physicists practicing in clinical settings are protected by laws and possess competent clinical knowledge in the field of Medical Physics. The services provided by medical physicists in healthcare facilities are regulated by standards set by the Minister of Health. Several cases involving quality issues related to radiology operational permits highlight the responsibilities of medical physicists in their practice. This research aims to examine the legal regulations governing the role of medical physicists in maintaining the quality of medical permits, the efforts made to address quality issues related to operational permits in hospitals, and the legal accountability of medical physicists in ensuring the quality of operational permits. The research employs a juridical empirical and normative methodology, collecting data through literature reviews, relevant laws, and interviews conducted at Bhayangkara Hospital in Banda Aceh. The research findings indicate that there are legal regulations concerning the role of medical physicists in maintaining the quality of radiology operational permits in hospitals, including regulations on nuclear safety issued by the regulatory body. In cases of errors involving medical physicists in hospitals, the hospital and the director are held responsible and may face administrative or criminal sanctions.